The first WHO global survey on infection prevention and control in health-care facilities. Issue 6 (June 2022) - Tomczyk, Sara; Twyman, Anthony; de Kraker, Marlieke E A; Coutinho Rehse, Ana Paula; Tartari, Ermira; Toledo, João Paulo; Cassini, Alessandro; Pittet, Didier; Allegranzi, Benedetta
Summary: Background: WHO core components for infection prevention and control (IPC) are important building blocks for effective IPC programmes. To our knowledge, we did the first WHO global survey to assess implementation of these programmes in health-care facilities. Methods: In this cross-sectional survey, IPC professionals were invited through global outreach and national coordinated efforts to complete the online WHO IPC assessment framework (IPCAF). The survey was created in English and was then translated into ten languages: Arabic, Chinese, English, French, German, Italian, Japanese, Russian, Spanish, and Thai. Post-stratification weighting was applied and countries with low response rates were excluded to improve representativeness. Weighted median scores and IQRs as well as weighted proportions (Nw) meeting defined IPCAF minimum requirements were reported. Indicators associated with the IPCAF score were assessed using a generalised estimating equation. Findings: From Jan 16 to Dec 31, 2019, 4440 responses were received from 81 countries. The overall weighted IPCAF median score indicated an advanced level of implementation (605, IQR 450·4–705·0), but significantly lower scores were found in low-income (385, 279·7–442·9) and lower-middle-income countries (500·4, 345·0–657·5), and public facilities (515, 385–637·8). Core component 8 (built environment; 90·0, IQR 75·0–100·0) and core component 2 (guidelines; 87·5, 70·0–97·5) scored the highest, and core component 7 (workload, staffing, and bed occupancy; 70·0, 50–90) and core component 3 (education and training; 70 ·0, 50·0–85·0) scored the lowest. Overall, only 15·2% (Nw: 588 of 3873) of facilities met all IPCAF minimum requirements, ranging from 0% (0 of 417) in low-income countries to 25·6% (278 of 1087) in primary facilities, 9% (24 of 268) in secondary facilities, and 19% (18 of 95) in tertiary facilities in high-income countries. Interpretation: Despite an overall high IPCAF score globally, important gaps in IPC facility implementation and core components across income levels hinder IPC progress. Increased support for more effective and sustainable IPC programmes is crucial to reduce risks posed by outbreaks to global health security and to ensure patient and health worker safety. Funding: WHO and the Infection Control Programme, University of Geneva Hospitals and Faculty of Medicine. Translations: For the French and Spanish translations of the abstract see Supplementary Materials section.